Israel Gohberg and Friends On the Occasion of his 80th Birthday - Bart, Harm.; Bart, Harm.; Hempfling, Thomas.; Hempfling, Thomas.; Kaashoek, Marinus A.; Kaashoek, Marinus A. (Birkhäuser Basel : Imprint: Birkhäuser, 2008)
This book is dedicated to Israel Gohberg on occasion of his 80th birthday on August 23, 2008. It is an expression of esteem and friendship for a great mathematician, a remarkable person and an inspiring colleague. The book contains reflections by Gohberg himself on his own mathematical activities and those of others. It also includes contributions of colleagues and co-workers, both from his time in the Soviet Union and from when he lived and worked in the West. The contributions in question are not mathematical research papers but focus on the man Israel Gohberg and are intended for a wide audience. To be found are letters, speeches, laudatios and reminiscences which, together, present an attractive picture of the way in which Israel Gohberg in the past four to five decades influenced the lives of many mathematicians. Biographical material such as a curriculum vitae, a list of publications, a list of Ph.D. students and information about honorary doctoral degrees is also included.